A Manual on Certification Requirements for School Personnel in the United States. 1970 Edition - Stinnett, T. M.; Pershing, Geraldine E.; National Association of State Directors of Teacher Education and Certification; National Education Association, Washington, DC. National Commission on Teacher Education and Professional Standards ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1970)
This latest edition (last in 1967) contains four chapters, the first a general discussion of "Innovations in Teacher Education, Certification, and Accreditation" dealing with the whole area of professional governance. Chapter 2 is a descriptive summary of "Preparation-Certification Standards and Procedures." Subtopics: Elementary Teachers, Secondary Teachers, Administrators; Fifth Year of Preparation; Increased Levels of Preparation; Significant Changes Since 1967; Personnel Required To Hold Certificates; Types of Certificates Issues; Separate-Name Certificates; Special Certification Programs; Special Teacher Education Programs; The Certification Authority; Misassignment of Teachers; Revocation of Certificates; Approved-Program Approach; Procedures for Out-of-State Applicants; Use of Examinations in Certification; Alternate Routes to Certification; Reciprocity in Certification; Teacher Education Accrediting Procedures; Control of State Colleges; Advisory Councils; Professional Practices Acts; Certification Review Committees; Chief Problems of the States; The Shape of Things to Come; Teaching in Canada. Chapter 3, the major section, is a listing of "Certification Requirements for Teachers, Supervisors, Administrators, and Special School Service Personnel" arranged by states and territories. Chapter 4 lists "Teacher Education Institutions and Approved Programs" by states. A list describing state advisory councils on teacher education (or comparable agencies) is appended. (JS)
Availability: Publication-Sales Section, National Education Association, 1201 Sixteenth St., N.W. Washington, D.C. 20036 (No. 381-11810; $6.00).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Accreditation (Institutions); State Standards; Teacher Certification; Teacher Education; Certification; Guides; School Personnel; Standards; United States